The implementation of reciprocal teaching strategy in teaching critical reading - Ika Dewi, Fitri Ana (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2023)
Low students’ interest in learning and reading English text influence to their critical reading ability. Teaching strategy is one of the solutions to solve the problem. An appropriate teaching strategy can influence to students’ interest in learning and reading English text. This study aims at describing the effect of reciprocal teaching strategy in teaching Critical and Evaluative Reading at second grade students of UIN Raden Mas Said Surakarta in the academic year of 2022/2023. Reciprocal teaching strategy consists of four activities, namely predicting, questioning, clarifying, and summarizing. The subjects are two classes of the second-grade students of English Education Study Program that consist of 60 students. The study used descriptive qualitative approach. Data were derived from observation and semi-structure interviews to the lecturer and students. The findings showed that the sequence activities of reciprocal teaching strategy encourage them to be more active and critical during teaching learning process. The activities that were done through working in group and sharing each other ideas help them overcome their difficulty during reading and facilitate them to be independent readers.